Professional adaptation of university students in the changing world of professions - P. A. Ambarova; G. E. Zborovsky (Образование и наука)
Introduction. The relevance of the problem of the article is determined by the need to improve approaches to the professional adaptation of university students in the conditions of rapid changes in the world of work and professions. The subject of the study is various forms of professional adaptation of students.Aim. The present research aims to identify the forms of university students’ professional adaptation, which have the greatest potential for adapting students to the future profession. The hypothesis of the study was the assumption that one of the new and effective forms of professional adaptation of students at the university can be their project activities.Methodology and research methods. The research methodology was mainly based on the community-based and activity-based approaches. The empirical basis of the article is the results of the research on the adaptation of students in Russian universities (2022 May–June). The conducted research was implemented using the methods of online survey, focus group, semi-formalised interview.Results. The main results of the study are the following: characteristics of the forms of professional adaptation of students at the university, the assessment of its main background factors, as well as the development by students of the norms of the academic environment as a predictor of mastering work and professional ethics, the problems of implementing project activities as a new form of adaptation to the profession. The scope of application of the research results is the practice of university project training and the development of programmes for professional students’ adaptation.In conclusion, project-based learning is considered as one of the most promising forms of students’ professional adaptation, the potential of which is not fully used. An important conclusion of the authors is that there is the need to focus student projects on an external customer in order to create a situation of students’ real immersion in the professional environment.Scientific novelty. The authors considered new forms of professional adaptation of students at the university and justified the significance of the revealed adaptation forms.Practical significance. The practical significance of the article is the possibility of using the results and conclusions of the study in the elaboration of university adaptation programmes for students and the improvement of their professional adaptation practices.